The Influence of Cultural and Family Factors on Gender Discrimination in Female Entrepreneurs - Hayu Latifah Aini; Ifah Rofiqoh (Jurnal Syntax Transformation, 2025)
Gender discrimination still occurs today where the differences in opportunities received by women and men still occur, but the discussion regarding women who experience gender discrimination has various causal factors in the discussion, namely due to cultural and family factors from various countries and different family backgrounds, starting from the Greek era to RA Kartini's struggle in an effort to equalize education and women's rights in social and family life is the main focus in the discussion. Gender discrimination using egalitarian theory where the theory includes justice as equality in this case, namely equality to obtain the same education and the right or opportunity to start a business as a female entrepreneur. it can be concluded that culture and family influence women's opportunities to obtain equal education and their rights to become female entrepreneurs, and this occurs in several countries.